Religious Movement of Movement of Ugamo Malim in Batak Land-Indonesia - Exson Pane; Freddy Manurung (Fakultas Filsafat Universitas Advent Indonesia, 2022)
Religious movements developed during the Dutch colonial period in Indonesia. One of the religious movements, Ugamo Malim, emerged in Batak land, North Sumatra, Indonesia.One of the reasons behind the religious movement in Indonesia during colonialism was to revive the holy king among the people to fight colonialism. However, the movement of Ugamo Malim was not ended after independence but continually recently. Therefore, this research tries to clarify the purpose of the establishment of the Ugamo Malim movement in Batak lands and the important things that we can learn from this movement as Christians. In order to get the clarification of this movement the author uses qualitative research by using documentary research analysis of Batak’s literature regarding the movement of Ugamo Malim and compare it to the Biblical principles. As the result the study found that before the colonialism Ugama Malim was existed as the way to have a pure life, however when colonialist came the purpose of this movement became formed as a movement in against the colonization and their religion which was brought to Batak Land. For today, the purpose of Ugamo Malim is to conserve the Batak’s culture, ceremonies, and practices in Batak’s Land. Although Ugamo Malim and Biblical principles is different, however there are several similarities in beliefs and practices such as worship God as they called “Mula Jadi Nabolon” (the creator), the day of worship is Saturday, forbidden eating blood and several unclean food as written in the Leviticus 11. Therefore, the main purpose of the movement of Ugamo Malim was to reach the pure life but it developed due to the coming of colonialism and modernity.